Allosteric pyruvate kinase-based "logic gate" synergistically senses energy and sugar levels in Mycobacterium tuberculosis. Issue 1 (December 2017) - Zhong, Wenhe; Cui, Liang; Goh, Boon; Cai, Qixu; Ho, Peiying; Chionh, Yok; Yuan, Meng; Sahili, Abbas; Fothergill-Gilmore, Linda; Walkinshaw, Malcolm; Lescar, Julien; Dedon, Peter
Abstract Pyruvate kinase (PYK) is an essential glycolytic enzyme that controls glycolytic flux and is critical for ATP production in all organisms, with tight regulation by multiple metabolites. Yet the allosteric mechanisms governing PYK activity in bacterial pathogens are poorly understood. Here we report biochemical, structural and metabolomic evidence thatMycobacterium tuberculosis (Mtb) PYK uses AMP and glucose-6-phosphate (G6P) as synergistic allosteric activators that function as a molecular "OR logic gate" to tightly regulate energy and glucose metabolism. G6P was found to bind to a previously unknown site adjacent to the canonical site for AMP. Kinetic data and structural network analysis further show that AMP and G6P work synergistically as allosteric activators. Importantly, metabolome profiling in the Mtb surrogate, Mycobacterium bovis BCG, reveals significant changes in AMP and G6P levels during nutrient deprivation, which provides insights into how a PYK OR gate would function during the stress of Mtb infection. Pyruvate kinase (PYK) controls glycolytic flux. Here, the authors combine biochemical, structural and computational modelling studies to characterize the allosteric mechanisms regulatingMycobacterium tuberculosis PYK activity and show that AMP and glucose-6-phosphate are synergistic allosteric activators of the enzyme.